2006
DOI: 10.1165/rcmb.2005-0462oc
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in the Carbohydrate Binding Preferences of Surfactant Protein D

Abstract: Interactions of surfactant protein D (SP-D) with micro-organisms and organic antigens involve binding to the trimeric neck plus carbohydrate recognition domain (neck+CRD). In these studies, we compared the ligand binding of homologous human, rat, and mouse trimeric neck+CRD fusion proteins, each with identical N-terminal tags remote from the ligand-binding surface. Although rat and mouse showed similar affinities for saccharide competitors, both differed markedly from the human protein. The human neck+CRD pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 31 publications
8
91
0
Order By: Relevance
“…These findings suggest that simultaneous binding of SP-D to multiple glycans on IAV HA is likely to increase the overall affinity of binding and therefore antiviral activity. Single-site deletion of Asn 177 , but not Asn 172 , reduced sensitivity to mouse BAL/SP-D and increased virulence in mice, a finding that may reflect differences in ligand specificity between human and mouse SP-D (52). Of interest, different collectins also display a distinct specificity for oligosaccharides expressed on IAV.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that simultaneous binding of SP-D to multiple glycans on IAV HA is likely to increase the overall affinity of binding and therefore antiviral activity. Single-site deletion of Asn 177 , but not Asn 172 , reduced sensitivity to mouse BAL/SP-D and increased virulence in mice, a finding that may reflect differences in ligand specificity between human and mouse SP-D (52). Of interest, different collectins also display a distinct specificity for oligosaccharides expressed on IAV.…”
Section: Discussionmentioning
confidence: 98%
“…We were unable to detect any competition for SP-D binding from lam- To test the hypothesis that SP-D interacts with more than one ligand on the surfaces of C. neoformans cells, we examined the abilities of GXM, MP1, and pustulan to inhibit SP-D binding to the encapsulated H99 strain and the acapsular cap59⌬ mutant. We found that all competitors, as well as many sugars known to bind the CRD domain of SP-D with variable affinities (11,12,37), inhibited SP-D binding to H99 cells to a much greater extent than that to cap59⌬ cells (Fig. 4).…”
Section: Sp-d But Not Sp-mentioning
confidence: 88%
“…Furthermore, differing interactions with these side chains contribute to known differences in saccharide selectivity. For example, the preference of human SP-D for D-N-acetylmannosamine over D-mannose can be attributed to hydrogen bonding of the Asp-325 carboxyl group with the N-acetyl substituent of the sugar (15,24).…”
Section: Surfactant Protein D (Sp-d)mentioning
confidence: 99%